Application for Suggesting Restaurants Using Clustering Algorithms - Iulia Alexandra IANCU; Eugenia IANCU (Journal of Applied Computer Science & Mathematics, 2014)
The aim of this article is to present an application whose purpose is to make suggestions of restaurants to users. The application uses as input the descriptions of restaurants, reviews, user reviews available on the specialized Internet sites and blogs. In the application there are used processing techniques of natural language implemented using parsers, clustering algorithms and techniques for data collection from the Internet through web crawlers.